Pengaruh Pendidikan Kewirausahaan terhadap Minat Berwirausaha pada Perguruan Tinggi Vokasi - Herdiansyah, Dedi; Fahrizal, Meizi; Suprihartini, Lia (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The level of entrepreneurship in Indonesia remains low at approximately 3.47%, far below the 12% target required to achieve the status of a developed country. Since 2008, the government has encouraged higher education institutions to integrate entrepreneurship courses with the aim of producing competent young entrepreneurs. The purpose of this study is to analyze the influence of entrepreneurship education on the entrepreneurial interest of students at Politeknik Negeri Pontianak, specifically those who are recipients of the Entrepreneurship Grant and winners of the Entrepreneurship Program. The method used is a mixed method, combining a quantitative approach with regression analysis using SPSS and a qualitative approach through data reduction, data display, and verification techniques. The results show that entrepreneurial knowledge significantly influences entrepreneurial interest with a contribution of 42.4%, while the remaining influence comes from other factors. The drivers of entrepreneurial interest include passion, family support, youth entrepreneurship trends, and advances in digital technology. Conversely, the main inhibiting factors are limited time, limited production tools, and low team commitment. The conclusion emphasizes that entrepreneurship education plays a crucial role in fostering entrepreneurial interest, but the success of its implementation heavily depends on external environmental support.